THE ANALYSES OF BUSINESS PROCESS CONCEPTUAL MODEL BASED ON BUNGE-WAND-WEBER ONTOLOGY - Igor G. Fedorov (Статистика и экономика)
This article discusses the Bunge-Wand-Weber representation ontology that is widely used for business process modeling and in object oriented IT development. Based on the analyses of this ontology the concepts of process modeling framework are selected. The example shows how real world objects are mapped on these ontological concepts. The goal of this paper is to introduce the business process conceptual model, which is build based on the Bunge-Wand-Weber representation ontology.